Prevalence and Losses Caused by Red Rot (Colletotrichum falcatum) Disease in Sugarcane Grown in District Tando Muhammad Khan - Pir Arshad Ahmed Jan Sirhandi (ACADEMIA International Journal for Social Sciences, 2026)
Sugarcane is a major cash crop in Pakistan but production is limited by fungal pathogens, especially red rot (Colletotrichum falcatum). The aim of this study was to determine the incidence and yield losses of red rot in sugarcane fields of District Tando Muhammad Khan, Sindh. The study employed a quantitative field approach to assess disease incidence, severity, and their effects on yield components in the field. The findings showed red rot disease was prevalent throughout the study region, with incidence ranging from low to high in different fields and cane varieties. Disease severity was found to be positively correlated with yield losses, suggesting the later stages of the disease impacted cane weight, stalk height and the quality of sugar cane juice. Yield reduction was found to be significant, demonstrating the impact of the disease on farmers and sugar companies. Favorable environmental factors for disease development and progression included high humidity and moderate temperatures. This research underscores the need for a comprehensive disease management approach, including the development of resistant varieties, optimal cropping practices, and early detection techniques. Managing red rot disease is crucial to improve sugarcane yields and promote sustainable farming practices.